Analisis Aksesibilitas Website Lembaga Nonstruktural Indonesia Sebagai Implementasi Corporate Digital Responsibility terhadap e-Government - Hidayat, Hikmatiyar; Fridan, Ridzkia Muhammad; Widyaputra, Rayhan Azhar; Falatehan, Ahmad Dzikri; Rahardjo, Andrea Marcella; Rajakanya, Dominica Tzarina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Keeping up with technological advancements is certainly not an easy task, especially developments in the website accessibility sector. In fact, the concept of accessibility itself should pave the way for obtaining similar information for everyone, especially on public information websites such as non-structural institutions. However, researchers have found that non-structural institution websites still cannot be fully utilized by people with disabilities, so that the distribution of public information is hampered. This can happen due to a lack of understanding of Corporate Digital Responsibility (CDR). In this research, the researcher aims to analyze the accessibility of websites of non-structural institutions in Indonesia, so that website developers can improve the quality of accessibility. Researchers used Silktide Accessibility Checker to carry out automatic evaluations with WCAG 2.2 AAA standards. The number of websites studied was 60 non-structural institution websites where researchers found 34 types of violations which reached a total of 7,465 accessibility violations, grouped into 3 categories, namely Critical, Serious and Moderate. This matter is certainly very important for people who have various physical limitations in accessing non-structural institution websites. Therefore, it is necessary to carry out a review by the government to ensure that all community groups receive the same information.